From Ledger to Cloud: A Dynamic Capabilities View of Digital AIS and SME Performance - Novta Winkey Pradana; Muhammad Adnan Effendi Putra; Deasy Emalia; Trisna Gayatri (Jurnal Economic Resource, 2025)
This study maps the intellectual structure of research on digital accounting information systems and SME performance. Using a quantitative bibliometric approach, we analyze 1,000 journal articles indexed in Crossref from 2010 to 2025. We retrieved the data using Publish or Perish and visualized it in VOSviewer, generating network, overlay, and density maps. Three themes emerge: technological enablers, organizational capabilities, and performance outcomes. Interpreted through Dynamic Capabilities Theory, the results provide a process-based framework and highlight platforms, trust, and SME financing as future research priorities.